Association of genomic imbalances with resistance to therapeutic drugs in human melanoma cell lines - Neßling, Michelle; Schadendorf, Dirk; Lichter, Peter (Cytogenetics and cell genetics, 1999)
The reason why human malignant melanomas respond poorly to chemotherapy is not known. In an attempt to identify genes responsible for such resistance or sensitivity to therapeutic drugs, we studied the parental human melanoma cell line MeWo, as well as eight drug-resistant sublines of MeWo. These have low and high levels of resistance to four chemotherapeutic drugs with different modes of action: Vindesine, cisplatin, fotemustine and etoposide. Comparative genomic hybridizations with genomic DNA from these cell lines as probes revealed a number of chromosome gains and losses which occurred upon selective pressure during development of the sublines. The MeWo subline with high resistance to the topoisomerase II inhibitor, etoposide, exhibited the highest number of acquired chromosome imbalances. Interestingly, the two lines with high resistance to cisplatin and fotemustine, respectively, shared three additional imbalances, loss of 9p, loss of distal 12p and gain on distal 15q. The importance of these coincident imbalances is discussed.